Component Display Theory (CDT) Learning Model Design in Basic Physics Lectures - Muhammad Syahrul Kahar; Rahmatullah Bin Arsyad; Muhammad Fathurrahman; Mursalin Mursalin (Jurnal Penelitian Pendidikan IPA, 2023)
One learning model that encourages implementation is Component Display Theory (CDT) which educators can apply as a way to obtain optimal problem solving abilities. The urgency of research requires developing a CDT learning model by adding one aspect, namely Creation, which is expected to perfect the three existing aspects. The theoretical basis is constructivist and cognitive theory, where constructivism is a view that perceives activities in reorganizing, interpreting and creating knowledge. The aim of the research is to design a CDT model for physics learning? The method used in this research uses a Research and Development approach using a 4D model with stages including Define, Design, Develop & Disseminate. The research results explain that the results of the needs analysis show that the current use of the CDT learning model still needs to be designed clearly to encourage increased student understanding, especially in terms of problem solving skills. Based on the analysis data, it was found that there was a significant correlation between the ability to remember (Remember) and the ability to find problems in learning with a percentage of 50.9%. Furthermore, the ability to find and the ability to apply has a correlation of 66.7%. Therefore, it can be said that learning procedures using the CDT model contribute significantly to the construction of students' understanding so that when linked to creative abilities, students are able to better understand learning completely and comprehensively by 59.4%, which means it provides significance in increasing participants' problem solving skills. educate. On the other hand, the remembering stage, when linked to the creation stage, contributes to an increase which is categorized as quite low when compared to the other stages, amounting to 11.5%. Therefore, in implementing learning, there needs to be coherent and measurable learning management that can encourage increased student learning